Florida Solid and Hazardous Waste Regulation Handbook: Clean Water Act (CWA) - Michael T. Olexa; Aaron Leviten; Kelly Samek (EDIS)
The purpose of the Clean Water Act is to maintain and restore the quality of the waters of the United States. The definition of waters is broad, including all waters subject to tidal movements, reaching between states, or used in interstate or foreign commerce. This is EDIS document FE452, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published December 2003.